Investigación socioeconómica de la parroquia Monterrey, cantón La Concordia, provincia de Santo Domingo de los Tsachilas y alternativas para su desarrollo. - Guerrero Yanza, Christian Enrique (2014)
To determine the quality of life for a fraction of the country is taken as an object of study of its coastal parishes called Monterrey, located 15 miles from Canton La Concordia, belonging to the province of Santo Domingo de los Tsáchilas, has taken this parish in order to make the socio-economic research of this population and raise needed for their development alternatives, since it is a power abacalera within the country and yet has undergone some delays by the scarcity of its flagship product that is the abaca.